Análise dimensional e de correlação antropométrica do corpo adiposo da bochecha e de perfil de satisfação do paciente após bichectomia - Azoubel, Eduardo (2019)
The bucal fat pad surgery is a surgical procedure employed with the primary objective of solving functional problems, but its partial removal may be associated with aesthetic procedures to obtain the harmony of facial measures and compliance with aesthetic standards. However, the literature is scarce regarding scientific studies that substantiate the accurate knowledge about the adipose body of the cheek as well as about the aesthetic result in the long term from its removal. The objective of this experimental clinical trial was to analyze the bilateral measures of volume and weight of this mentioned structure, which were removed during the bichectomy procedure, seeking to correlate them with the anthropometric variables of the patients and to investigate if their removal promoted alteration of facial measures of volunteers after six months. We also analyzed aspects related to the patient satisfaction profile in the pre and postoperative period, as well as the complications associated with this procedure. For this purpose, 57 patients aged 19-47 years were enrolled to analyze the dimensions of the cheek fat body and anthropometric correlation. In the evaluation of pre and post operative facial measures, 20 volunteers were included. The results showed that there was no statistically significant correlation between the dimensions of the anatomical repair evaluated and the anthropometric measurements of the individuals enrolled in the analysis. Similarly, it was verified that there was no statistically significant difference of the facial measurements after the bichectomy (paired Student test, p <0.05). Regarding the satisfaction questionnaire, the descriptive analysis showed that self-perception regarding aesthetic necessity was the predominant factor in the indication of the surgery and that the majority of patients were satisfied with the results, which were close to the expected according to their self evaluation.